Acute neuromuscular paralysis, rhabdomyolysis and long lasting neurological deficits in Ceylon krait (Bungarus ceylonicus) bites: Two authentic cases from a serpentarium in Sri Lanka. (October 2019) - Kularatne, S.A.M.; Colombage, Anuradha; de Silva, Anslem; Weerasinghe, Vajira; Rathnayaka, R.M.M.K. Namal
Abstract: The Ceylon krait ( Bungarus ceylonicus ) is a highly venomous elapid snake endemic to Sri Lanka. Its bites are rare and only seven reports are found in the literature. Therefore, the clinical manifestations and natural history of envenoming of Ceylon krait are not well studied yet. Neuroparalysis is the main clinical manifestation of their bites. We report two cases of proven Ceylon krait bites of two young snake keepers working in a serpentarium. They developed acute neuroparalysis, abdominal pain and a period of amnesia. The first patient developed myalgia and increased level of serum creatine kinase suggestive of rhabdomyolysis. One was treated with Indian polyvalent antivenom and both recovered with some long-lasting clinical disabilities namely impairment of sensation of the bitten arm and persistent refraction errors in the eyes in the first patient. The second patient had persistent marked nystagmus. Highlights: Ceylon krait ( Bungarus ceylonicus ) is endemic to Sri Lanka and bites rarely. Two authentic bites are described. Both developed neuromuscular paralysis manageable without assisted ventilation. Long lasting deficits were sensory impairment of bitten arm, refraction errors and nystagmus.